Factor Analysis of Kemendikbud's Free Internet Quota on the Online Learning Process - Marshel Aditya Prayoga; Rinabi Tanamal (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
Covid-19 emerged from a widespread virus originated from the Wuhan, Chinese, which caused a pandemic on a large scale, and hit various countries, especially in Indonesia. The Covid-19 pandemic that hit Indonesia made several aspects of life change significantly, especially in the field of education. Changes in the educational process that were previously face-to-face, are transformed into distance learning or online. Various needs emerged in this online learning process, such as the availability of internet network access was not smooth, the problem of the cost of buying internet quota, and limits on access to internet quotas obtained. Kementerian Pendidikan dan Kebudayaan (Kemendikbud) as the regulator of learning activities in Indonesia, strives for the smooth running of online learning activities at all levels, by distributing internet data packages to educators and students. Based on program from Kemendikbud, this research is expected to see the various factors that influence in the free internet quota program affect the online learning process for students at Universitas Ciputra Surabaya. The method used to collect survey data in this study is a questionnaire, and determining respondents using simple random sampling method, instrument distributed online to 90 users of free internet quota from Kemendikbud, because the Covid-19 pandemic is still not over. After the required data has been collected, validity and reliability tests are carried out and hypothesis testing is carried out using the SEM-PLS method using SmartPLS 3.3.3 software. The results of the tests carried out stated that there was a positive and significant influence given by the Benefit (KB) variable on Online Learning (PD) with a relationship value of 0.476, then there was a positive but insignificant effect given by the Network Quality (KJ) variable on the Learning variable. Online (PD) with a relationship value of 0.113, then there is a positive and significant influence provided by the Ease (KM) variable on the Online Learning (PD) variable with a relationship value of 0.355.